2003
DOI: 10.1007/s101650300009
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix recovery by human articular chondrocytes after treatment with hyaluronan hexasaccharides or Streptomyces hyaluronidase

Abstract: The treatment of human articular chondrocytes with Streptomyces hyaluronidase (St-HAЈase) or hyaluronan hexasaccharides (HA 6 ) provides two approaches to the selective depletion of specific components of the extracellular matrix, and an opportunity to follow the reparative responses initiated by these changes. In this study, changes in the relative expression of messenger RNA for hyaluronan synthase-2, CD44, and aggrecan were determined by competitive, quantitative reverse transcriptasepolymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In RT-PCR analysis, the gene expressions of type II collagen and COMP were up-regulated by the treatment with HA 6 . Furthermore, expression of HA synthase 2 mRNA was increased 2.1-fold by HA oligosaccharides, and aggrecan mRNA was increased 1.8-fold by HA oligosaccharides in human articular chondrocytes (47). These results also suggest that anabolic responses, as evidenced by matrix synthesis, take place simultaneously with the catabolic responses induced by small HA oligosaccharides.…”
Section: Discussionmentioning
confidence: 62%
“…In RT-PCR analysis, the gene expressions of type II collagen and COMP were up-regulated by the treatment with HA 6 . Furthermore, expression of HA synthase 2 mRNA was increased 2.1-fold by HA oligosaccharides, and aggrecan mRNA was increased 1.8-fold by HA oligosaccharides in human articular chondrocytes (47). These results also suggest that anabolic responses, as evidenced by matrix synthesis, take place simultaneously with the catabolic responses induced by small HA oligosaccharides.…”
Section: Discussionmentioning
confidence: 62%
“…However, as discussed above, exposure of chondrocytes to IL-1α or IL-1β results in the stimulation of NO, MMP-13, HA synthase-2 (HAS-2) and CD44 but, a dramatic inhibition of aggrecan and type II collagen. HA oligos affect a stimulation of NO, MMP-13 and HAS-2 but, little change in CD44 and a stimulation of aggrecan and type II collagen Nishida et al, 2003;Ohno et al, 2005). In addition, whereas IL-1 mediated signaling terminates in an activation of AP-1 transcription factors, HA oligos affect no activation of AP-1 (Ohno et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, in vitro studies have demonstrated that HA oligosaccharides alter chondrocyte metabolism and induce chondrocytic chondrolysis. Enhanced MMP activity was observed after HA oligosaccharide treatment of both cartilage explants and chondrocytes in culture balanced by increased synthesis of both HA and aggrecan, but no change in expression of CD44 receptors (Nishida, Knudson, & Knudson, 2003;Ohno, Im, Knudson, & Knudson, 2005). Thus, disruption of HA-chondrocyte interactions by HA oligosaccharides initiates both anabolic and catabolic responses.…”
Section: Introductionmentioning
confidence: 96%
“…After removal of HA8, the cell-associated matrices of MG-63 and articular chondrocytes were recovered. 32 Recovery of LM-8 cell matrices following washout were also observed (data not Mouse LM8 osteosarcoma cells were transplanted subcutaneously into C3H/He mice. From day 14 to day 23, 250 g/ml HA4, HA8, HMWHA, or control medium was injected daily, directly into the tumor mass.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, investigators have used small oligosaccharides of HA to deplete HA-rich matrices from cells. 31,32 The proposed mechanism is that these small oligosaccharides compete with the binding of high-molecular-mass HA with cell surface receptors such as CD44. Given their size, purity, and ease of permeability into tissues, the use of such small oligosaccharides may have suitable clinical applicability.…”
mentioning
confidence: 99%